Professionalism in action – Music teachers on an assessment journey - Johan Nyberg (Educare)
The points of departure in this article are questions regarding assessment in music education. These are related to issues of professional responsibility and accountability as well as a holistic view on education as conceptualized in Deweyean pragmatism and concern the risk of criteria compliance. A participatory action research project in a Swedish Upper secondary school focusing on assessment of music is presented, where the purpose of the research was to develop knowledge about music teachers’ experience and conceptualizations regarding assessment practices within the frame of the National Arts Programme. This is enabled by asking the following research questions: In what ways do teachers conceptualize musical knowledge and learning and educational communication in relation to assessment? What qualities appear within the teachers’ conceptualizations regarding knowledge, learning, communication and assessment of students’ knowledge? Aims from the field of praxis were integrated in the project, with focus on equivalent assessment and legal certainty. Results from the research project show the music teachers’ ability to shift between atomistic and holistic perspectives but at the same time keep their holistic view of assessment and learning. Equivalence is according to the teachers something different than uniformity, and is only possible through reflection and collaboration, internally as well as externally with other practitioners.